A cysteine-less and ultra-fast split intein rationally engineered from being aggregation-prone to highly efficient in protein trans-splicing - Christoph Humberg; Zahide Yilmaz; Katharina Fitzian; Wolfgang Dörner; Daniel Kümmel; Henning D. Mootz (Nature Communications)
Abstract Split inteins catalyze protein trans-splicing by ligating their extein sequences while undergoing self-excision, enabling diverse protein modification applications. However, many purified split intein precursors exhibit partial or no splicing activity for unknown reasons. The Aes123 PolB1 intein, a representative of the rare cysteine-less split inteins, is of particular interest due to its resistance to oxidative conditions and orthogonality to thiol chemistries. In this work, we identify β-sheet-dominated aggregation of its N-terminal intein fragment as the origin of its low (~30%) splicing efficiency. Using computational, biochemical, and biophysical analyses, we characterize the fully active monomeric fraction and pinpoint aggregation-prone regions. Supported by a crystal structure, we design stably monomeric mutants with nearly complete splicing activity. The optimized CLm intein (Cysteine-Less and monomeric) retains the wild-type’s ultra-fast reaction rate and serves as an efficient, thiol-independent protein modification tool. We find that other benchmark split inteins show similar precursor aggregation, suggesting that this general phenomenon arises from the intrinsic challenge to maintain the precursor in a partially disordered state while promoting stable folding upon fragment association.